O‘QUVCHILARDA MEDIA SAVODXONLIK KO‘NIKMASINI SHAKLLANTIRISH («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
21st century skills are a set of knowledge, life and professional skills, habits that are of decisive importance in the modern world, especially for the young generation to step into a big life and succeed. These skills are also called life skills. Paying special attention to the education of students in general secondary education, preparing them for life by forming the skills of the 21st century, preventing violations that occur in schools, independently solving problems that arise in various situations, teaching them to fight against violence, motivational solutions to the issues of leadership, media literacy, inculcating global citizenship skills in young people is one of the urgent issues of today. This article talks about the formation of media literacy, which is a part of life skills in mother tongue (Uzbek language) education.
Keywords: 21st century skills, mother tongue education, media literacy, artificial intelligence, social networks, audio text, spelling literacy.